Association between operation volume and postoperative mortality in elective endovascular repair of infrarenal abdominal aortic aneurysms: systematic review - continuation - Ronellenfitsch, Ulrich; Meisenbacher, Katrin; Ante, Marius; Grilli, Maurizio; Böckler, Dittmar (Gefässchirurgie, 2020)
Many surgical interventions show an inverse association between case volume per hospital/surgeon and perioperative mortality. In the first part of this systematic review it was shown that such an association also exists for the open treatment of infrarenal aortic aneurysms. The second part now examines a possible association with endovascular treatment of infrarenal aortic aneurysms.
Gesehen am 06.12.2021